2016
DOI: 10.3390/met6120318
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microstructure on Strength and Ductility in Fully Pearlitic Steels

Abstract: This article deals with the relationship between the microstructure and both strength and ductility in eutectoid pearlitic steel. It is seen how standard mechanical properties and fracture micromechanisms are affected by heat treatment and the resulting microstructure in the material. The yield stress, the ultimate tensile strength and the ductility (measured by means of the reduction in area) exhibit a rising trend with the increasing cooling rate (associated with smaller pearlite interlamellar spacing and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The fracture surface of specimens after annealing (Figure 15) shows the typical features of a ductile fracture, confirming the mechanical behavior evidenced in the stress-strain curves. It also is possible to observe in Figure 15b the fracture surfaces of pearlitic grains [42]. Brittle failure could be observed in the case of austempered specimen (Figure 17), with the development of cleavage facets [31], highlighted in the figure by circles.…”
Section: Microhardness Testmentioning
confidence: 87%
“…The fracture surface of specimens after annealing (Figure 15) shows the typical features of a ductile fracture, confirming the mechanical behavior evidenced in the stress-strain curves. It also is possible to observe in Figure 15b the fracture surfaces of pearlitic grains [42]. Brittle failure could be observed in the case of austempered specimen (Figure 17), with the development of cleavage facets [31], highlighted in the figure by circles.…”
Section: Microhardness Testmentioning
confidence: 87%
“…The microstructure of pearlitic steel mainly includes the prior austenite grain, pearlite colony, and interlamellar spacing. Many investigators have carried out extensive research on the relationship between the microstructure and mechanical properties [2][3][4][5]. These results showed that refining the microstructure of pearlite steel has become a general point of view to improving its comprehensive mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, finer pearlite microstructures comprising smaller colony size and shorter interlamellar spacing, show a more ductile fracture character. This one is represented by a larger number of dimples as well as a smaller share of ferrite/ cementite lamellae in the fracture process zone [11].…”
Section: Effects Of Molybdenum Alloying In Cast Ironmentioning
confidence: 99%